Perlindungan Hukum Konsumen Terhadap Pembelian Produk Handbody Dosting pada E-Commerce Shopee - Cahya Andika; Hidayati, Nuri; Mardiyana (Rechtsregel : Jurnal Ilmu Hukum, 2025)
The ability to purchase goods online has greatly simplified consumers’ access to desired products, including body lotion and other personal care items. However, if this convenience is not carefully monitored by the relevant regulatory authorities, it may pose risks to public health. This study aims to identify the factors contributing to the increasing use of high-dose body lotions to achieve instant beauty results, as well as to explore strategies for reducing the number of individuals harmed by the use of such products. The research employs a normative juridical approach, which focuses on assessing existing legal norms designed to protect consumers. The findings indicate that many women today adhere to beauty standards that emphasize having light skin, encouraging them to compete in purchasing and using high-dose body lotions without adequately understanding the product ingredients, which are clearly harmful to the skin when used over a prolonged period. Many high-dose body lotion products widely available on e-commerce platforms contain hazardous substances at concentrations exceeding the safety limits established by the Food and Drug Supervisory Agency (BPOM). The use of high-dose body lotions may cause skin irritation and damage skin tissue. Consumers’ awareness of the risks associated with high-dose body lotion products remains low. Therefore, authorities with the appropriate regulatory powers should provide public education, conduct product destruction, and carry out market inspections as measures to prevent future harm.